Generalized Anxiety Disorder Among Pregnant Women Attending Antenatal Clinic at Primary Health Care Ungwar Rimi, Kaduna State (Western Journal of Medical and Biomedical Sciences, 2023)
Pregnancy is a major physiological change in the life of a woman. It is often accompanied by emotional disorders, including anxiety disorder.1 The concerns and worries about the health of the unborn child could be enormous and some women are known to suffer psychological distress at this time.2 Most studies assessing the correlates of anxiety among pregnant women in Nigeria were mainly carried out in tertiary health institutions in Southern Nigeria, leaving out those that attend Primary Health Care (PHC) centres. The objective of this study was to determine the prevalence and correlates of Generalized Anxiety Disorder (GAD) among pregnant women seeking antenatal care at the PHC Centre in UngwarRimi, Kaduna State. One hundred and fifty women at various stages of pregnancy, aged twenty years and above were randomly selected and interviewed by PHC workers using the 7-items Generalized Anxiety Disorder (GAD-7) and the author used the Anxiety module of Structured Clinical Interview for DSM (Diagnosis and Statistical Manual of Mental) Disorders (SCID) to assess the same participants. The prevalence of GAD identified by the PHC workers was 15.3%. The prevalence rate recorded using more elaborate SCID was 10.7%. No significant statistical difference between the two rates was found. Determinants of GAD among the subjects were primigravida (OR= 4.32; 95% CI 3.21 – 8.20), previous adverse pregnancy outcome (OR=2.40; 95% CI 1.00 – 8.15), partner violence (OR = 3.15; 95% CI 1.22 – 7.56). GAD is common in pregnancy and routine screening for anxiety disorder during antenatal care using simple, easily administered tool like GAD-7 could help to identify those at risk even by primary health workers. Prompt referral to psychiatry for management will improve overall wellbeing of women in pregnancy.
Keywords: GAD; Antenatal care; PHC